Utilização da ferramenta análise de perfil em larvicultura de Botia (Botia lohachata) - Silva, Rafaele Motta (2013)
This task was performed at the Aquaculture Laboratory of Animal Husbandry and Animal Nutrition North Fluminense State University conducted with the objective of making the profile analysis of two variables: weight and length Botia, Botia lohachata, comparing six moments of life according with feeding. A total of 24 experimental units, each with 10 liters of water and continuous renewal. Each unit experimental received 10 larvae per liter with a total of 2,400 larvae in all the experimental units. We tested six treatments with four replications. The treatments constituted the following food handling: T1 - diet, T2, T3 and T4 formed by feeding with Artemia sp in 4, 8, and 12 days respectively after the feeding period was accomplished by replacing ration, T5 - Artemia. Were used as live food Artemia franciscana newly hatched larvae. The analysis was performed by comparing two of the two treatment depending on the desired variable providing treatment which provides higher final weight and length. Thus it was seen feeding on Artemia only showed higher final weight and length when compared to other diets and treatments that possessed a longer period of co-feeding gave higher results (p <0.05) than treatment with only diet and an improved co-feed period.